Aggressiveness and emotional state in students of Institutions Educational Services of Metropolitan Lima - Prado Verdi, Marlon Manuel Omar (2018)
Correlative descriptive comparative type research that aimed to determine the levels of aggressiveness - emotional state and establish the relationship and comparison of aggressiveness and emotional state depending on the sex and type of family to which they belong. For this purpose, a sample of 343 school children from the 1st to 4th year of secondary school, of both sexes, from two educational institutions in Metropolitan Lima, the Buss-Durkee Hostility Aggression Inventory (1987) and the self-perception scale of the emotional state (Vila Doris - Díaz Luis, 2007). The data were processed in the statistical program SPSS version 22.0 in Spanish and the following conclusions were reached: In aggressiveness, 18.1% of the studied sample presented levels of aggressiveness ranging from the high level to the excessive level. In emotional state, 28.5% of the sample presented moderate levels at high levels. A very significant positive moderate relationship between aggressiveness and emotional state is found. In emotional state there are no differences depending on the sex.